Tathbīqul Istirātijiyyatil Mumti'ah fī Ta’līmi Qowāidil Lughatil Arabiyyah lil Athfāl - Maturedy, Faris; Ahmad Nahid Mashury (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2023)
The Nahwu teachers of Al Mawarits An Nabawiyyah Islamic Boarding School are confronted with the issue of waning enthusiasm towards the acquisition of Arabic grammar knowledge. To address this issue, the use of joyful learning strategies is employed, utilizing games in conjunction with the Uno Stacko medium. The objective of this study is to illustrate the utilization of joyful learning strategies in the context of Nahwu learning activities. This study utilizes a qualitative research approach, specifically employing a case study methodology. Data was collected by researchers through the process of observing and conducting interviews with Nahwu teachers. The data underwent analysis using a three-stage process that involved reduction, description, and drawing conclusions. The researchers reached the conclusion that the teachers engaged in a discourse over a pedagogical approach. Consequently, the pedagogical strategy of joyful learning was implemented through the utilization of games using Uno Stacko. The implementation of the happy learning technique has the potential to rekindle students' enthusiasm for the study of Nahwu. This phenomenon is evidenced by the active engagement of students during educational activities within the classroom setting.